Protein Quality of the Bacterium Hydrogenomonas eutropha - Calloway, Doris H. (1969)
Hydrogenomonas eutropha cells harvested from semicontinuous autotrophic culture and washed free of substrate contain about 13% of nitrogen on a dry-solids basis. Biological value and digestibility of the bacterial nitrogen were determined in the rat by use of an abbreviated Mitchell-Thomas nitrogen balance technique and casein as the standard protein. Casein nitrogen was 99% digestible, and that of both whole boiled and sonically ruptured bacterial cells was 93%. Biological value of casein and the bacterial preparations was uniformly 77%. Amino acid composition of the bacteria, as in the case of casein, indicates a first limitation of sulfur-containing amino acids. These compositional features suggest that H. eutropha may be potentially valuable as a protein supplement in animal feeds.